Comparative Analysis of Social Work Curricula in Asia: Recommendations for Curriculum Development in Cambodia - Somchan, Socheata; Kyung Yang, Ok (Asian Social Work Journal, 2024)
Despite growing recognition of the need for social workers, Cambodia is still at beginning stage in establishing a standardize system recognizing the social service workforce which is an important factor providing direction for social work education development. This paper compares social workforce development frameworks and curricula in developed countries like Korea and developing countries like Thailand to suggest improvements for curriculum development in Cambodia. The research aimed to assess the strengths and limitations of social work curricula in the region and identify effective methods for advancing social work education in Cambodia. The analysis of the social work curriculum using curriculum frameworks such as Curriculum Design and Content, Pedagogical Approaches, Field education, and Accreditation and Registration Systems provides a descriptive analysis of the current state of social work curricula in Korea, Thailand, and Cambodia. Nine recommendations for Cambodia's Social Work Curriculum Development include establishing a well-defined licensure and certification framework, expanding elective courses to focus on specific areas of interest, preserving practicum hours, enhancing collaborations with local social service organizations, including interdisciplinary courses, customizing curriculum material to meet local socioeconomic demands, providing ongoing professional development opportunities for social work educators, enhancing Competency-Based Education by prioritizing skills in line with local contexts, and promoting community involvement through community-based projects and activities.